2016
DOI: 10.17507/jltr.0706.14
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Phonological and Grammatical Awareness on EFL Students' Reading Performance

Abstract: Abstract-The purpose of the present research was to assess the influence of phonological and grammatical awareness on reading performance of EFL students at Azad Islamic University of Kerman. Based on such a purpose, a series of linguistic tasks were applied in order to find the relationship between phonological and grammatical awareness and reading performance. 50 EFL students participated in the present study through a qualitative and quantitative survey. Phonological awareness was measured by four tasks whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 27 publications
(17 reference statements)
1
6
0
Order By: Relevance
“…It was supported by Azar (2007), understanding of English grammar helps many students formulate how to say what they mean and helped them lead to successful communication. In addition, Jafari (2016) claimed that student who had grammatical skills and were able to use their grammatical awareness more efficiently, paid much more consideration to the strategies for improvement of reading performance. Moreover, other participants felt that understanding English grammar was difficult.…”
Section: The Discussion About Student Teachers' Perception Towards Grmentioning
confidence: 99%
“…It was supported by Azar (2007), understanding of English grammar helps many students formulate how to say what they mean and helped them lead to successful communication. In addition, Jafari (2016) claimed that student who had grammatical skills and were able to use their grammatical awareness more efficiently, paid much more consideration to the strategies for improvement of reading performance. Moreover, other participants felt that understanding English grammar was difficult.…”
Section: The Discussion About Student Teachers' Perception Towards Grmentioning
confidence: 99%
“…This consists of several elements: the integration of the sender's intention, situational factors and contextual knowledge in a communicative process where CLT may further prompt meaning and pragmatic factors in a communicative situation. CLT and CLIL demand more contextual learning, so they take into account pragmatic awareness as predominant language awareness, whereas GTM only underlines phonological and morphological awareness (Jafari & Rad, 2016).…”
Section: Language Awareness Reading Comprehension and Foreign Languamentioning
confidence: 99%
“…In order he/she can judge whether or not their students' works are correct. Related to the grammar knowledge, teacher's explicit knowledge of grammar is a need which enables them to teach effectively in either productive or receptive skills (Andrews, 2007;Su'ib, 2009;Jafari & Rad, 2016). Explicit knowledge refers to the knowledge about grammar by unsderstanding the rule.…”
Section: Explicit Knowledge To Raise Grammatical Awarenessmentioning
confidence: 99%
“…As Gozali & Harjanto (2014) in their study of grammatical awareness in the context of EFL kindergarten teacher mentioned that most of students in one particular private kindergarden school has higher speaking ability,but lack in grammatical competence. In different language skills, such as reading skills, there was also found that students grammatical awareness could affect students' reading outcome (Su'ib, 2009;Jafari & Rad, 2016).…”
Section: Introductionmentioning
confidence: 99%